Kinetic study of non-isothermal co-pyrolysis of tyre crumb with eucalyptus sawdust. (2018) - Cherop, Peter T.; Kiambi, Sammy L.; Musonge, Paul
The non-isothermal model-free and model-fitting kinetics of co-pyrolysis of tyre crumb (TC) with eucalyptus sawdust (ESD) was investigated in this study. The thermogravimetric analysis (TGA) was conducted at heating rates of 2, 5 and 10°C min –1 in nitrogen environment at a temperature ramp of 20-600°C. The data from TGA was employed to determine the activation energies (E) by applying Ozawa-Flynn-Wall (OFW) and Friedman (FR) models, while the pre-exponential factors were determined using the Coats-Redfern (CR) method. The average activation energies obtained were 150.29 kJ/mol and 147.29 kJ/mol using OFW and FR methods respectively. The relationship between E and conversion degree, as evidenced by goodness-of-fit tests, appeared to be of sixth degree polynomial kind. The first, second, and third reaction order mechanisms yielded mean pre-exponential factors of 2.73E+03 min –1, 1.72E+06 min –1 and 5.54E+09 min –1 respectively. Results indicate that the first order reaction model best describes the co-pyrolysis mechanism.